The Effect of Asset Growth on Company Profitability with Sales Growth and Leverage as Supporting Variables - Hadi Utomo, Kukuh; Widhiastuti, Susanti (DINASTI RESEARCH, 2024)
A method commonly employed to assess a company's proficiency in generating profits involves the calculation of its profitability ratio. This ratio, in turn, can be affected by various factors, such as the growth of assets, sales expansion, and the level of leverage. The study utilised a population of 89 samples drawn from 18 retail sub-sector companies listed on the Indonesia Stock Exchange (IDX) over the period from 2018 to 2022. This research is characterised as explanatory in nature, employing a quantitative approach and utilising purposive sampling criteria. The data collection was conducted through a combination of literature reviews and observational studies, with the testing method involving multiple linear regression analysis, which was performed using the IBM SPSS version 20 software. (1) Partially asset growth has no effect on profitability; (2) Partially sales growth has no effect on profitability; and (3) Partially leverage affects profitability. Based on these findings, the authors suggest that company management should give due consideration to the leverage factor, as it has been demonstrated to have a significant impact on the company's profitability.